SOCIO-ECONOMIC DEVELOPMENT ON THE BASIS OF OVERCOMING INEQUALITY - Nadtochii , A.; Smahliuk , A. (Theory and Practice of Public Administration, 2020)
The views on inequality from the point of view of the theory of liberalism and egalitarianism are considered. From the standpoint of the theory of liberalism, inequality is the natural state of affairs for which each person must be responsible, because all have equal opportunities. The only thing the government is responsible for is just ensuring equal opportunities for everyone. From the standpoint of egalitarianism, inequality is not a natural phenomenon. In this case, it is the responsibility of the government to ensure to every person not only has equal opportunity but equal results too. The causes and consequences of inequality are identified. It is stated that excessive inequality has many negative social and economic consequences. Thus, the main negative consequence of excessive income inequality is that the rich are able to make decisions in their own favor. This undermines the foundations of democracy and preserves a state of affairs when people from the lower levels of society cannot get to power; there are no social elevators. This leads to the fact that the ruling elite will not get outsiders, there will be no new ideas, and thus economic growth will decline. The origins of inequality in Ukraine are considered. The origins of inequality in Ukraine are presented. Ukraine is a country from the post-Soviet space in which visible equality was observed, but in reality there was an inequality associated with belonging to a certain elite, primarily political, ideological. Ukraine has inherited the hidden inequality. So today, according to the official data, inequality in Ukraine is at the minimal level. According to the Palmа Ratio, Ukraine is the leader in the ranking of the most equal societies. It has been found that Ukrainian scientists explain this phenomenon with insufficient quality of sample studies (on the basis of which the inequality indicators are calculated) and the neglect of shadow incomes. An analysis of recent trends in Ukraine has shown that inequality is rising primarily due to higher incomes in the highest positions in the public sector. In order to reduce income inequality in Ukraine, it is proposed to restore progressive income taxation and increase social standards, including the subsistence minimum and the minimum wage.